2018
DOI: 10.1088/1755-1315/111/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Dust Concentrations over Desert and Cropland during Dust Storms Using Visibility Sensors

Abstract: Abstract. Directly measuring the dust concentration during a dust storm is very important for studying dust emission and wind erosion processes. The Mira visibility sensors were introduced for directly measuring dust concentrations over desert and cropland during dust storm events. The output of the sensor was compared with that of optical particle counter. We found that the Mira visibility sensors can directly measure the particle numbers concentrations. Characteristics of dust concentrations at the two groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…According to the data analysis in this research, the wind velocity surrounds biomimicry conceptual building model is lower than basic building models resulting the dust concentration deposited on the building envelope lower as well. Based on Figure 19, higher wind speed results in higher Dust Concentration Index (DCI) [41]. According to the data analysis in this research, the wind velocity surrounds biomimicry conceptual building model is lower than basic building models resulting the dust concentration deposited on the building envelope lower as well.…”
Section: Matrix Tabulation Analysismentioning
confidence: 68%
See 1 more Smart Citation
“…According to the data analysis in this research, the wind velocity surrounds biomimicry conceptual building model is lower than basic building models resulting the dust concentration deposited on the building envelope lower as well. Based on Figure 19, higher wind speed results in higher Dust Concentration Index (DCI) [41]. According to the data analysis in this research, the wind velocity surrounds biomimicry conceptual building model is lower than basic building models resulting the dust concentration deposited on the building envelope lower as well.…”
Section: Matrix Tabulation Analysismentioning
confidence: 68%
“…For slope sides building model such as pyramids, the data analysis showed that the degree of slope is directly proportional to self-cleaning efficiency percentage. The relationship between the degree of slope and self-cleaning efficiency percentage is described in the Figure 10 below: Based on Figure 11, higher wind speed results in higher Dust Concentration Index (DCI) [41]. According to the data analysis in this research, the wind velocity surrounds biomimicry conceptual building model is lower than basic building models resulting the dust concentration deposited on the building envelope lower as well.…”
Section: Matrix Tabulation Analysismentioning
confidence: 78%